1999
DOI: 10.1046/j.1523-1755.1999.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of hyperhomocysteinemia in hemodialysis and peritoneal dialysis

Abstract: Hyperhomocysteinemia is more prevalent and intense in HD patients compared with those on PD. The homocysteine response may become refractory to excess folate supplementation in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 23 publications
6
64
1
3
Order By: Relevance
“…10 Similarly, many studies have reported that hHcys still occurs in ESRD patients receiving hemodialysis therapy. 3,9,11 In some patients with hypertension, in addition, a long-term diuretic therapy resulted in hHcys, but their GFR or renal functions were normal. 5,15 All these data indicate that elevated plasma tHcys levels in the patients with ESRD or hypertension may not depend on a decrease in GFR.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, many studies have reported that hHcys still occurs in ESRD patients receiving hemodialysis therapy. 3,9,11 In some patients with hypertension, in addition, a long-term diuretic therapy resulted in hHcys, but their GFR or renal functions were normal. 5,15 All these data indicate that elevated plasma tHcys levels in the patients with ESRD or hypertension may not depend on a decrease in GFR.…”
Section: Discussionmentioning
confidence: 99%
“…Födinger et al [22]have reported that MTHFR VV genotype, serum albumin, and plasma folate influence the plasma homocysteine level, but that gender, plasma vitamin B 12 , and serum creatinine do not. Several studies [28, 29, 30]have shown that the plasma homocysteine concentration shows significant negative correlations with plasma vitamin B 12 and plasma folate concentrations in patients on hemodialysis. However, the exact mechanism of hyperhomocysteinemia in hemodialysis patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indeed demonstrated that clinically stable renal transplant recipients have an excess prevalence of hHcys, suggesting that improvement of the GFR in these patients does not completely restore plasma Hcys to normal [9, 29]. Similarly, in ESRD patients receiving hemodialysis therapy, improvement of the renal function could not restore plasma Hcys concentrations to normal levels [35, 36]. In some patients with hypertension, moreover, long-term diuretic therapy results in hHcys, but their GFR or renal functions are normal [3].…”
Section: Hhcys and Esrdmentioning
confidence: 99%